ECHO: Shards of sound - Lima, Aretha Brito de; Andrade, Eduardo dos Santos; Schiavoni, Flávio Luiz (Anais do Simpósio Brasileiro de Computação Musical, 2025)
This work is far more than just a sound sculpture or a digital musical instrument. It is, above all, an exercise in sonic memory — a living archive of Belo Horizonte’s urban soundscape. Through the act of listening and collecting, the city is mapped not by its streets or architecture, but by its acoustic textures, its rhythms, its voices, and the ephemeral sonic events that compose daily life. In an urban context where sound is often perceived as pollution — an unwanted residue of modern existence — this work proposes a different way of listening. It invites the audience to engage with the acoustic chaos of the city, not as mere noise, but as a carrier of meaning, memory, and identity. What is usually dismissed as sonic debris — engines, footsteps, metallic reverberations, overlapping conversations — becomes raw material for poetic reconstruction. Each sound fragment functions as a shard, a broken piece of the city’s auditory landscape. As participants rearrange these fragments, they build an ever-changing mosaic of stories, invisible geographies, and collective memories. What was once perceived as disorder transforms into an intimate, tactile, and deeply human experience of sound, space, and presence.